Arterial tortuosity in patients with spontaneous cervical artery dissection - Giossi, Alessia; Mardighian, Dikran; Caria, Filomena; Poli, Loris; De Giuli, Valeria; Costa, Paolo; Morotti, Andrea; Gamba, Massimo; Gilberti, Nicola; Ritelli, Marco; Colombi, Marina; Sessa, Maria; et al. (Neuroradiology, 2017)
Purpose The aim of this study was to test the hypothesis that patients with spontaneous cervical artery dissection (CeAD) have increased arterial tortuosity, and the objective quantification of such a tortuosity may aid in the identification of subjects at increased risk of disease. Methods In the setting of a hospital-based, case-control study, we used the vertebral tortuosity index (VTI) measured on magnetic resonance angiography, a validated method for the assessment and quantification of arterial tortuosity, to compare the degree of tortuosity in a series of consecutive patients with spontaneous CeAD and of age- and sex-matched patients with ischemic stroke unrelated to CeAD (non-CeAD IS) and stroke-free subjects. Results The study group was composed of 102 patients with CeAD (mean age, 44.5 ± 7.8 years; 66.7% men), 102 with non-CEAD IS, and 102 stroke-free subjects. The VTI was higher in the group of patients with CeAD (median, 7.3; 25th–75th percentile, 10.2) compared with that of non-CeAD IS (median, 3.4; 25th–75th percentile, 4.4) and of stroke-free subjects (median, 4.0; 25th–75th percentile, 2.9; p ≤ 0.001), and was independently associated to the risk of CeAD (OR, 1.18; 95% CI, 1.09–1.29) in multivariable regression analysis. The degree of tortuosity also tended to be higher in CeAD patients who experienced short-term recurrence (5.8%; median, 20.2; 25th–75th percentile, 31.2) than in those without recurrent events (median, 7.2; 25th–75th percentile, 9.4; p = 0.074). Conclusion CeAD patients exhibit increased arterial tortuosity. This might have potential implications for better understanding of the pathophysiology of the disease as well as clinical utility in evaluation, prognostication, and decision-making of affected individuals.